PENGARUH KOMPENSASI DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN PT. PEGADAIAN CABANG PALOPO - Wahyudi, Wahyudi; Sukri, Sukri; Hadrah, Hadrah (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
This study aims to determine the influence of compensation and career development on employee performance at PT. Pegadaian Palopo Branch. The research design used is explanatory with a quantitative approach. Data were collected through questionnaires distributed to 34 employees of PT. Pegadaian Palopo Branch. The collected data were then analyzed using multiple linear regression to identify the relationships between variables. The results of the study indicate that compensation has a partially positive and significant influence on employee performance. Career development also has a partially positive and significant influence on employee performance. Simultaneously, compensation and career development together have a positive and significant influence on employee performance.